2022
DOI: 10.1039/d2an00925k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of illicit pills and drugs of abuse in urine samples using a 3D-printed open port probe hyphenated with differential mobility spectrometry-mass spectrometry

Abstract: The present work describes the application of an in-house developed 3D-printed open port probe (3DP-OPP) with differential ion mobility spectrometry (DMS) mass spectrometry. Targeted quantitative analysis in urine was perfomed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…compatible with general ESI ion sources) and reduce costs (~3 euros per piece of OPP), we produced devices with 3D printers and used them to qualitatively and/or quantitatively study metabolomics samples, thus eliminating carryover but retaining high speed sample introduction. 45,46 In the present study, we report a method that can differentiate true PMIs from the non-specific binding that is usually observed in native ESI-MS analysis. The method exploits the advantage of the OPP that the solvent can easily and continuously changed from native (NH 4 Ac solution)…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…compatible with general ESI ion sources) and reduce costs (~3 euros per piece of OPP), we produced devices with 3D printers and used them to qualitatively and/or quantitatively study metabolomics samples, thus eliminating carryover but retaining high speed sample introduction. 45,46 In the present study, we report a method that can differentiate true PMIs from the non-specific binding that is usually observed in native ESI-MS analysis. The method exploits the advantage of the OPP that the solvent can easily and continuously changed from native (NH 4 Ac solution)…”
Section: Introductionmentioning
confidence: 98%
“…The open port probe (OPP) was proposed by Van Berkel et al 42 and its application has been extended in various area. [43][44][45] The core structure of the OPP is two coaxial tubes, the outer one receives solvents from pumps and the inner one aspirates samples into the electrospray ion source. 42,46 Samples can be independently introduced by pipette, syringe pump, or autosampler onto the dome of the OPP and are instantly aspirated into the ion source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gómez-Ríos et al reported a fast quantitation of opioids isomers in human plasma using biocompatible solid-phase micro extraction (bio-SPME) and an open-port probe sampling interface 15 . Sosnowski et al 16 describe the application of an in-house 3D-printed open port probe (3DP-OPP) with DMS-MS for the quantitative analysis of cocaine and tramadol isomeric metabolites in urine samples and for the screening of illicit ecstasy pills using acetonitrile as modifier. While most DMS applications have been established on systems running at atmospheric pressure, a prototype DMS working at low pressure range 4.7-30 Torr was recently developed, employing a planar-gap stage within the MS instrument envelope rising normalized electric field up to 543 Td 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The major benefit of DIA is the possibility of re-interrogating the sample post-acquisition for qualitative or quantitative analysis. The combination of scanning DMS with a large SWATH window has been reported by Sosnowski et al [ 16 ] and enabled the differentiation of isobaric signals from illicit drugs with a large dynamic range and enhanced the information contained in these pills by acquiring MS2-level information.…”
Section: Introductionmentioning
confidence: 99%